A Prospective Study on Prevalence of Conginetal Heart Diseases in Children with Down Syndrome - Ahmad Bilal, Wahab Qadir, Qamar Uz Zaman, Shagufta Niazi, Quratulain Shaikh, Fahad Nazir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Down syndrome (DS) is the most prevalent genetic disorder in humans around the globe. Variations in pattern and risk factors for congenital heart diseases significantly contributes to the increasing morbidity and mortality among Down syndrome children. The present study aimed to determine the prevalence of congenital heart diseases among Down syndrome children. Methodology: This prospective study was carried out on 46 Down syndrome children in the Department of Pediatric, Shalamar Hospital Lahore from November 2020 to June 2022. The study protocol was approved by the research and ethical committee. Demographic details, outcomes, and diagnosis on echocardiography were extracted from the proforma and medical record. Data such as date of birth, maternal age, parity, and parental consanguinity were collected. Antenatal history such as obesity, maternal passive smoking, and diabetes confirmed the antenatal infections. Data regarding children including gender, birth weight, maturity, and plurality were considered. For data analysis, SPSS version 25 was used. Results: Of the total 46 Down syndrome children, there were 29 (63%) male and 17 (37%) females. The overall mean age was 3.61±2.3 years with an age range from 0 to 15 years. Majority of the Down syndrome children 32 (69.6%) were under 5 years followed by 9 (19.6%) in 5-10 years and 5 (10.8%) in between 10 and 15 years. The prevalence of congenital heart disease was 26 (56.5%) in Down syndrome children. Of the total 26 Down syndrome children with congenital heart disease, the incidence of cyanotic and acyanotic heart disease were 5 (10.8%) and 21 (45.7%) respectively. Out of 56.5% cases of congenital heart disease, ventricular septal defect (VSD) was the most prevalent congenital heart disease found in 12 (46.2%) cases followed by Atrio-venticular canal defect 7 (26.9%), Tetralogy of fallot 4 (15.4%), and atrial septal defect 3 (11.5%). Conclusion: Our study concluded that the prevalence of congenital heart disease was 56.5% among Down syndrome children. Majority of congenital heart diseases were acyanotic. Male are more susceptible to congenital heart diseases. Ventricular septal defect (VSD) was the most prevalent congenital heart disease. Early diagnosis, referral, and prompt intervention can prevent congenital heart diseases among Down syndrome children. Keywords: Congenital heart diseases, Prevalence, down syndrome children